Early Marriages and Pupil's Academic Performance in Butanda Sub- County Kabale District. - Katushabe, Sharlote (Kabale University, 2024)
Early marriage is a symbol of poor orientation. Throughout the world. marriage is regarded as a moment of celebration and a milestone in one's life. Sadly. the practice of early marriage involves the deprivation of fundamental human rights. Young girls are robbed of their youthfulness and required to take roles. they are not emotionally prepared for. Majority of the young girls have no choice about the timing of marriage or their partner. The purpose' of the study was to establish the factors influencing early marriages in Butanda Sub Count), Kabale district.